Rolling Pampas agroecosystem: which landscape attributes are relevant for determining bird distributions - Weyland, Federico (2014)
Background: Agricultural intensification is among the main factors affecting biodiversity. The Rolling Pampas of Argentina have undergone through a process of landscape transformation and agricultural intensification that altered avian diversity patterns. Grassland area loss is argued to be the main reason for grassland bird species declines, but there is a lack of studies that compare cropland vs. pastures including other landscape features as determinants of species richness and distribution. Also, it is needed to understand how these relations are modified at different spatial scales. In this study, we explored how species are associated to different landscape attributes and elements like land use, roadside vegetation, trees, homesteads, and water bodies. Our aim was to explore how bird species are associated to the new elements of the Pampas agroecosystem at different spatial scales to reveal which are important for avian management. Results: We ran field surveys covering a range of land use and landscape complexity, defined by the variety of component features. We performed canonical correspondence and diversity partition analyses to determine the association of species with land use, landscape complexity, and particular anthropogenic elements. Our results show that land use type is an important driver of bird species distributions, but it is also controlled by the presence of trees, houses, and water bodies that provide nesting and food resources. Simple landscapes have higher species turnover rates (beta diversity) than complex ones with similar gamma diversity, demonstrating that the effect of landscape simplification on bird diversity differs across spatial scales, leading to different possible management and conservation strategies. Conclusions: New approaches are needed to manage agroecosystems for avian conservation. We need to take pragmatic approaches, and in highly disturbed ecosystems, anthropic elements have to be included as constituent parts of the system.